PERANCANGAN SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN PENETAPAN DOSEN PEMBIMBING DAN PENGUJI TUGAS AKHIR DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Karyo Budi Utomo; Ansar Rizal (Politeknik Negeri Samarinda, 2016)
Decision-making by decision makers today is getting easier. Various instruments supporting data can be served quickly and appropriately to the leaders the organization as a supporting material in decision making. And in support of decision making in setting a course supervisor and examiner final project will require the support of accurate data as a reference for the study program managers in determining the appropriate supervisor and examiner. So that the target to maintain the quality of student research can be optimized. Method of decision-support system is very diverse, but in this study the authors using Analytical Hierarchy Process (AHP). Some of the reasons for the author to use such methods include: 1). Its hierarchical structure, as a result of the selected criteria, sub-criteria until the very end; 2) .Calculate validity up to the limit of tolerance inconsistency of various criteria and alternatives selected by the decision makers; 3) .calculate sensitivity analysis of decision-making. The results of this research is the design of decision support systems in the determination of the supervisor and examiner Student final project using Analytical Hierarchy Process (AHP). Process flow that occurs does not change from the previous flow that has been running, and the determination of criteria can be done dynamically, which is adjusted to the needs of the determination of the supervisor and examiner final project at that time. Kata Kunci : AHP, Pengambilan Keputusan,Tugas Akhir, Pembimbing, Penguji